Plastid phylogenomic insights into relationships of all flowering plant families - Li, Hong-Tao; Luo, Yang; Gan, Lu; Ma, Peng-Fei; Gao, Lian-Ming; Yang, Jun-Bo; Cai, Jie; Gitzendanner, Matthew A.; Fritsch, Peter W.; Zhang, Ting; Jin, Jian-Jun; Zeng, Chun-Xia; et al. (BMC biology, 2021)
Flowering plants (angiosperms) are dominant components of global terrestrial ecosystems, but phylogenetic relationships at the familial level and above remain only partially resolved, greatly impeding our full understanding of their evolution and early diversification. The plastome, typically mapped as a circular genome, has been the most important molecular data source for plant phylogeny reconstruction for decades. Here, we assembled by far the largest plastid dataset of angiosperms, composed of 80 genes from 4792 plastomes of 4660 species in 2024 genera representing all currently recognized families. Our phylogenetic tree (PPA II) is essentially congruent with those of previous plastid phylogenomic analyses but generally provides greater clade support. In the PPA II tree, 75% of nodes at or above the ordinal level and 78% at or above the familial level were resolved with high bootstrap support (BP ≥ 90). We obtained strong support for many interordinal and interfamilial relationships that were poorly resolved previously within the core eudicots, such as Dilleniales, Saxifragales, and Vitales being resolved as successive sisters to the remaining rosids, and Santalales, Berberidopsidales, and Caryophyllales as successive sisters to the asterids. However, the placement of magnoliids, although resolved as sister to all other Mesangiospermae, is not well supported and disagrees with topologies inferred from nuclear data. Relationships among the five major clades of Mesangiospermae remain intractable despite increased sampling, probably due to an ancient rapid radiation. We provide the most comprehensive dataset of plastomes to date and a well-resolved phylogenetic tree, which together provide a strong foundation for future evolutionary studies of flowering plants.